2008
DOI: 10.1029/2007jd008392
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycle of C16O16O, C16O17O, and C16O18O in the middle atmosphere: Implications for mesospheric dynamics and biogeochemical sources and sinks of CO2

Abstract: Here we present a two-dimensional simulation of the isotopic composition of CO 2 from the surface to an altitude of $130 km that adequately reproduce the observed seasonal cycle of CO 2 in the upper troposphere and the age of air in the stratosphere. Our model results suggest that stratospheric-tropospheric exchange not only modifies the level of heavy CO 2 in the troposphere, but also influences its seasonal cycle. Thus the isotopic composition of CO 2 in the troposphere/biosphere could be affected by the dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 76 publications
5
39
0
Order By: Relevance
“…The elevated anomaly compares well with the average value found in 10 years of measurements made at La Jolla, CA, USA (Thiemens et al 2014). Liang et al (2008a) extended this model and suggested that the stratospheric-tropospheric exchange modifies the isotopic composition of CO 2 , and also influences its seasonal cycle. The results from a phase correlation study of O 3 and CO supported this conclusion and suggested that the stratosphere-troposphere exchange carries stratospheric air into the troposphere at select places (Liang et al 2008b).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The elevated anomaly compares well with the average value found in 10 years of measurements made at La Jolla, CA, USA (Thiemens et al 2014). Liang et al (2008a) extended this model and suggested that the stratospheric-tropospheric exchange modifies the isotopic composition of CO 2 , and also influences its seasonal cycle. The results from a phase correlation study of O 3 and CO supported this conclusion and suggested that the stratosphere-troposphere exchange carries stratospheric air into the troposphere at select places (Liang et al 2008b).…”
Section: Introductionsupporting
confidence: 62%
“…MIF in stratospheric ozone (Mauersberger 1981;Thiemens et al 1991) is thought to be partially transferred into carbon dioxide (Thiemens et al 1995;Hoag et al 2005;Liang et al 2007Liang et al , 2008a (Thiemens et al 1991;Yung et al 1997;Lämmerzahl et al 2002;Boering et al 2004). Note that the photochemical processes involving O 2 , O 3 , and CO 2 introduce the positive anomaly in CO 2 and also a small corresponding negative anomaly in O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratospheric oxygen isotope covariations in CO 2 (8,11,12) consistently differ from those found in laboratory experiments simulating stratospheric photochemistry (6,(13)(14)(15)(16) Table 1). The stratospheric samples display ⌬ 47 values both higher and more variable than those exhibited by tropospheric air at the surface, which has an average ⌬ 47 value of 0.92 Ϯ 0.01‰ in remote regions (Cape Grim, Tasmania and Barrow, Alaska) (18).…”
mentioning
confidence: 72%
“…In the stratosphere, the oxygen isotopic composition of CO 2 is thought to be modified by oxygen isotope exchange reactions with O( 1 D) generated by ozone photolysis (2), whereas in the troposphere it is controlled by isotope exchange reactions with liquid water in the oceans, soils, and plant leaves (3). The interplay between stratospheric and tropospheric isotope exchange reactions, in principle, could allow the relative abundances of 12 (4,5), but the stratospheric CO 2 photochemical system is still underconstrained, and our understanding of it is incomplete.…”
mentioning
confidence: 99%